ANALYSIS OF THE ROLE OF RESERVATION SYSTEMS IN IMPROVING CUSTOMER EXPERIENCE IN THE SALON AND SPA INDUSTRY: LITERATURE REVIEW - Permatasari, Hanifah; Purwanto, Eko; Triyono (LPPM Universitas Duta Bangsa Surakarta, 2023)
This research paper aims to analyze the role of reservation systems in enhancing the customer experience in the salon and spa industry through a comprehensive literature review. The study adopts a qualitative research approach utilizing a systematic review of relevant academic articles, books, and research reports. The research focuses on identifying the benefits and challenges associated with reservation systems, as well as best practices and trends in the industry. The findings contribute to the understanding of the impact of reservation systems on customer experience and provide recommendations for improving reservation system effectiveness in the salon and spa industry.